Tests of German Resilience - Bornhorst, Fabian (IMF Working Papers; Working Paper ;, 2012)
From its early post-war catch-up phase, Germany's formidable export engine has been its consistent driver of growth. But Germany has almost equally consistently run current account surpluses. Exports have powered the dynamic phases and helped emerge from stagnation. Volatile external demand, in turn, has elevated German GDP growth volatility by advanced countries' standards, keeping domestic consumption growth at surprisingly low levels. As a consequence, despite the size of its economy and important labor market reforms, Germany's ability to act as global locomotive has been limited. With increasing competition in its traditional areas of manufacturing, a more domestically-driven growth dynamic, especially in the production and delivery of services, will be good for Germany and for the global economy. Absent such an effort, German growth will remain constrained, and Germany will play only a modest role in spurring growth elsewhere.